The profit impact of business intelligence - Williams, Steve; Williams, Nancy (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2007)
Business Intelligence (BI): Its not just a technology. Its not just a methodology. Its a powerful new management approach that when done right can deliver knowledge, efficiency, better decisions, and profit to almost any organization that uses it. When BI first came on the scene, it promised a lot but often failed to deliver. The missing element was the business-centric focus explained in The Profit Impact of Business Intelligence. Written by BI gurus Steve Williams and Nancy Williams, The Profit Impact of Business Intelligence shows step by step how you can achieve the promise of BI by connecting it to your organizations strategic goals, culture, and strengths while correcting your BI weaknesses. Features: * Provides a practical, process-oriented guide to achieve the full promise of BI. * Shows how world-class companies used BI to become leaders in their industries. * Helps senior business and IT executives understand the strategic impact of BI and how they can ensure a strong payoff from their BI investments. * Identifies the most common mistakes organizations make in implementing BI. * Includes a helpful glossary of BI terms. * Includes a BI readiness assessment for your organization. * Includes Web links and extensive references for more information. Steve Williams, President and founder of DecisionPath Consulting, is a leading advocate of business-driven BI design and development. His consulting firm is one of the largest in the specialized field of Business Intelligence and Data Warehousing. Steve has over 23 years experience in information systems and systems engineering and has co-authored a training course on the BI Pathway Method. Nancy Williams is Vice President of DecisionPath Consulting. With over 21 years of business and technical experience, she provides technical and strategic leadership on business intelligence as well as hands-on guidance for client engagements. * A practical, process-oriented book that will help organizations realize the promise of BI * Written by Nancy and Steve Williams, veteran consultants and instructors with hands-on, "in the trenches" experience in government and corporate business intelligence applications * Will help senior business and IT executives understand the strategic impact of BI and how they can help ensure a strong payoff on BI investments.
The business value of business intelligence -- Identifying and prioritizing business intelligence-driven opportunities for your organization -- Business intelligence readiness : prerequisites for leveraging business intelligence to improve profits -- Business-centric business intelligence development with the BI pathway method -- Leading and managing a business intelligence-driven profit improvement program -- Business intelligence in the broader information technology context -- Important ways business intelligence can drive profit improvement -- Common mistakes companies make on business intelligence initiatives -- A view over the horizon -- Appendix A : A business intelligence glossary -- Appendix B : A business intelligence readiness assessment.
Includes bibliographical references (p. 206-207) and index.
Keywords: Business intelligence; Profit; Electronic books